Utilization of Red Dragon Fruit (Hylocereus polyrhizus) Peel Waste as an Alternative Indicator for Acid - Base Titration - Azkiya, Noor Isnaini; Sukmawanta, Shafara Najla Marinda; Lusiani, Cucuk Evi (Politeknik Negeri Malang, 2025)
Titration indicators are organic (generally) or inorganic compounds used in titrations to determine and indicate the end point of a titration. Indicators that are widely used in acid-base titrations are synthetic indicators such as phenolphthalein (PP), methyl red (MM), methyl orange (MO), and phenol red (MF). Apart from being relatively expensive, the use of these indicators also produces chemical waste which can pollute the environment. The solution to overcome this problem is to utilize natural ingredients as a substitute for synthetic indicators. The natural indicator used in this research was the peel of red dragon fruit (Hylocereus polyrhizus). Red dragon fruit peel contains flavonoid compounds, one of which is anthocyanin. Anthocyanins are polar so they can be dissolved in polar solvents such as ethanol. This research aims to determine the effect of the type of solvent and length of maceration time in anthocyanin extraction as an indicator for strong acid-strong base titration, and to determine the effect of storage time on the stability of red dragon fruit peel extract. In the maceration process, a variable ratio of solvent to red dragon fruit peel was used 1:5 (w/v). The solvents used were ethanol, methanol, and acetone acidified with 5 mL of HCl 1% (v/v). Identification of anthocyanin compounds was carried out using FT-IR and UV-Vis. In this study, the highest anthocyanin content was found in the acetone solvent 9x10-4 mg/100 g and the lowest was in the methanol solvent at 6x10-4 mg/100 g. Furthermore, the most similar application to a commercial titration indicator is the use of methanol and acetone solvents with a 24-hour extraction time.